2007
DOI: 10.1016/j.ygcen.2006.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic and tissue-specific regulation of myostatin-1 and -2 gene expression in zebrafish

Abstract: Myostatin is a member of the TGF-β superfamily and a potent negative regulator of muscle growth and development in mammals. Its expression is limited primarily to skeletal muscle in mammals, but occurs in many different fish tissues, although quantitative measurements of the embryonic and tissue-specific expression profiles are lacking. A recent phylogenetic analysis of all known myostatin genes identified a novel paralogue in zebrafish, zfMSTN-2, and prompted the reclassification of the entire subfamily to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 45 publications
3
40
0
1
Order By: Relevance
“…Mstn K/K mice (Lin et al 2002), which is consistent with increased negative feedback on pituitary GH, the primary regulator of liver size (Ohlsson et al 2009). Myostatin's role in the spleen is unknown, although it is minimally expressed in the spleens of zebrafish and mice and is significantly upregulated when the former are stressed (Helterline et al 2007). No cellular phenotype was detected in any of these tissues, indicating that the differences were likely due to tissue hypoplasia or atrophy.…”
Section: Aging Mice Young Adultsmentioning
confidence: 99%
“…Mstn K/K mice (Lin et al 2002), which is consistent with increased negative feedback on pituitary GH, the primary regulator of liver size (Ohlsson et al 2009). Myostatin's role in the spleen is unknown, although it is minimally expressed in the spleens of zebrafish and mice and is significantly upregulated when the former are stressed (Helterline et al 2007). No cellular phenotype was detected in any of these tissues, indicating that the differences were likely due to tissue hypoplasia or atrophy.…”
Section: Aging Mice Young Adultsmentioning
confidence: 99%
“…While, both transcripts of MSTN a and b were detected as early as post-fertilization of eggs, the level of expression was observed to increase during embryonic development and reached a peak near hatching in barramundi (Lates calcarifer) (De Santis et al, 2012). Although several studies had reported detection of MSTN a transcripts during early development, only in zebrafish (D. rerio) the distinct regulation of the two subtypes had been comparatively analyzed during embryogenesis (Helterline et al, 2007). In this study, both the expression levels of MSTN a and MSTN b were significantly higher than their expression levels before hatching.…”
Section: Genesmentioning
confidence: 99%
“…Similarly, our results showed that there were remarkably low expressions from 20 to 90 dph (except at 30 dph), it then increased significantly and reached its maximum at 150 dph (P < 0.05). This indicated that the 90 dph stage of Chinese perch development could be a rapid growth stage due to its association with an intense myoblast proliferation and hypertrophy, which mainly contributed to skeletal muscle growth, but also controlled the number of muscle fibers by inhibiting myoblast proliferation in cattle embryos (Helterline et al, 2007) and tilapia, gilthead seabream, and post-hatch larvae of Chilean flounder (Delgado et al, 2008). A recent report indicated that the expression levels in 7-day old larvae of Walking catfish were higher than those in 2-month old juveniles, unchanged from 2-month old juveniles to 6-month old juveniles, and then increased significantly in adult fish of 1-3 years of age (Kanjanaworakul et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…In tilapia, MSTN gene expression was observed in the brain and particularly in the optic lobe (Rodgers et al, 2001). In adult zebrafish, the MSTN gene was expressed highly in all tissues except the eye and gall bladder (Helterline et al, 2007). In the barramundi, it was also observed in various tissues including the skeletal muscles, gills, heart, blood, kidneys, and intestines (De Santis et al, 2008).…”
Section: Discussionmentioning
confidence: 99%